Effect of critical medium components and culture conditions on antitubercular pigment production from novel Streptomyces sp D25 isolated from Thar desert, Rajasthan - Radhakrishnan Manikkam, Gopikrishnan Venugopal, Balagurunathan Ramasamy, Vanaja Kumar (Journal of Applied Pharmaceutical Science, 2015)
Effect of culture conditions and critical medium components on antitubercular pigment production from novel Streptomyces sp D25 isolated from Thar desert, Rajasthan was investigated. Antitubercular pigment from Streptomyces sp. D25 was produced by Agar Surface Fermentation (ASF) using yeast extract malt extract agar (YEME) as a basal medium. Effect of incubation period, temperature, carbon source, nitrogen source, minerals and sodium chloride concentration was studied by adopting one-variable-at-a-time method. Crude pigment produced under different conditions was extracted solid-liquid extraction method using ethyl acetate. Responses measured include the growth rate, quantity of crude extract and activity against S. aureus MTCC96 and M. tuberculosis H37Rv at 100 µg concentrations. Growth and pigment production was correlated with the bioactivity. Of the various conditions tested, maximum growth, pigmentation and bioactivity was observed on 6th day of incubation. Of the various medium components tested, 1% glucose, fructose and malt extract, pH 7 and 9, temperature 300C and 400C, 0.1% KNo3 and 0-5% NaCl was found to influence the growth, bioactive pigment production and antimicrobial bioactivity. Further statistical based optimization is in progress to prove the effect of interaction of the above variables on antitubercular pigment production from Streptomyces sp D25.
Keywords: Streptomyces, Thar desert, agar surface fermentation, one-variable-at-a-time, antitubercular.